ANALISIS EFISIENSI FAKTOR – FAKTOR PRODUKSI USAHA TANI TEMBAKAU RAKYAT KABUPATEN TEMANGGUNG - Adistia Nurul Huda Hardanis; Dwisetia Poerwono (Universitas Diponegoro, 2014)
Temanggung regency is one of the largest producers of tobacco in Central Java Province. Development of tobacco farming experience various problems that productivity declined and unstable prices. This research aim to analyze the relationship between production factors to the quantity of production and analyze the efficiency of production factors tobacco farming in Temanggung Regency. The analysis model used is the Cobb-Douglass production and frontier production function. This research used primary data through interviews to tobacco farmers using questionnaires and secondary data as supporting research. Data were analyzed by multiple regression analysis and frontier production function in order to determine the production factors efficiently. The result showed that the variables of seed and pesticide Dursban are not significant and have a positive effect, dung and ZA fertilizerhave a significant positive effect, and labor is negative significant effect on the amount of tobacco production in Temanggung Regency. Value of technical efficiency in this study was 0.9447. This figure is less than 1, the technique is inefficient and use of factors of production needs to be reduced. Level of price efficiency is also inefficient, because the value is greater than 1 is 3,996, so it is necessary to add production factors in order to achieve the optimum level. Both technical efficiency and price efficiency is inefficient, causing the value of economic efficiency is also inefficient. Return to Scale the result is equal to 0,639. This suggests that the tobacco farm follow the rules of decreasing returns to scale.